Environmental manipulations generate bidirectional shifts in both behavior and gene regulation in a crossbred mouse model of extremes in trait anxiety - Chekmareva, Natalia Y.; Sotnikov, Sergey V.; Diepold, Rebekka P.; Naik, Roshan R.; Landgraf, Rainer; Czibere, Ludwig (Frontiers in Behavioral Neuroscience, 2014)
Although gene-environment interactions are known to significantly influence psychopathology-related disease states, only few animal models cover both the genetic background and environmental manipulations. Therefore, we have taken advantage of the bidirectionally inbred high (HAB) and low (LAB) anxiety-related behavior mouse lines to generate HABxLAB F1 hybrids that intrinsically carry both lines’ genetic characteristics, and subsequently raised them in three different environments – standard, enriched (EE) and chronic mild stress (CMS). Assessing genetic correlates of trait anxiety, we focused on two genes already known to play a role in HAB vs. LAB mice, Crhr1 and Hmgn3. While EE F1 mice showed decreased anxiety-related and increased explorative behaviors compared to controls, CMS has sparked effects in the opposite direction. However, environmental treatments affected the expression of the two genes in distinct ways. Thus, while expression ratios of Hmgn3 between the HAB- and LAB-specific alleles remained equal, total expression resembled the one observed in HAB vs. LAB mice, i.e., decreased after EE and increased after CMS treatment. On the other hand, while total expression of Crhr1 remained unchanged between the groups, the relative expression of HAB- and LAB-specific alleles showed a clear effect following the environmental modifications. Thus, the environmentally driven bidirectional shift of trait anxiety in this F1 model strongly correlated with Hmgn3 expression, irrespective of allele-specific expression patterns that retained the proportions of basic differential HAB vs. LAB expression, making this gene a match for environment-induced modifications. An involvement of Crhr1 in the bidirectional behavioral shift could, however, rather be due to different effects of the HAB- and LAB-specific alleles described here. Both candidate genes therefore deserve attention in the complex regulation of anxiety-related phenotypes including environment-mediated effects.